Injectable gellan gum hydrogels with autologous cells for the treatment of rabbit articular cartilage defects - Oliveira, J. T. (2010)
In this work, the ability of gellan gum hydrogels coupled with autologous cells to regenerate rabbit full-thickness articular cartilage defects was tested. Five study groups were defined: (a) gellangumwith encapsulated chondrogenic predifferentiated rabbit adipose stem cells (ASCþGF); (b) gellan gum with encapsulated nonchondrogenic predifferentiated rabbit adipose stem cells (ASC); (c) gellan gum with encapsulated rabbit articular chondrocytes (AC) (standard control); (d) gellan gum alone (control); (e) empty defect (control). Fullthickness articular cartilage defects were created and the gellangum constructs were injected and left for 8 weeks. The macroscopic aspect of the explants showed a progressive increase of similarity with the lateral native cartilage, stable integration at the defect site, more pronouncedly in the cell-loaded constructs. Tissue scoring showed that ASCþGF exhibited the best results regarding tissue quality progression. Alcian blue retrieved similar results with a better outcome for the cell-loaded constructs. Regarding real-time PCR analyses, ASCþGF had the best progression with an upregulation of collagen type II and aggrecan, and a downregulation of collagen type I. Gellan gum hydrogels combined with autologous cells constitute a promising approach for the treatment of articular cartilage defects, and adipose derived cellsmayconstitute a valid alternative to currently used articular chondrocytes.